Determinasi Tarif Retribusi Pasar Tradisional dengan Pendekatan Willingness To Pay Dan Perbandingan Harga Pasar - Pitri Yandri (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
The new autonomous region is generally faced with the administrative adaptation problem. The adaptation is being implemented by South Tangerang Municipality. One of the adaptations is doing traditional market governance improvement to become better by setting the tarif of retribution. In theoretically, the approach to the determinate of tarif retribution can be analyzed by the variety of approaches. Two of the most widely used is the willingness to pay and market price comparative approach. Thus, this article will use those approaches to estimate traditional market tariff retribution. The results of the estimation and its elaboration are discussed further in this article